Identity and inter religious understanding in Jewish schools in England. Issue 1 (2nd January 2016) - Ipgrave, Julia
Abstract : This article sets up a dialogue between auto -referential (looking to self) and allo -referential (looking to the other) approaches to religious difference and applies these to education for inter religious understanding in Jewish schools. It begins by arguing that the multiculturalism of the 1980s and 1990s set up a duality of self and other, with the responsibility for looking to 'the other' ( allo -reference) resting largely on the majority community and the licence to look to self ( auto -reference) being given to minority communities . Within the Jewish community, multiculturalism supported and legitimated the development of an inward-looking Jewish identity-based education. This was challenged in the 2000s however by the new outward-looking emphases of the community cohesion agenda, and so Jewish schools have had to negotiate a place for themselves between auto - and allo -reference. Brief case studies illustrate contrasting ways in which two schools have positioned themselves in relation to these two poles. In School A, the imperative towards 'the other' attempts an openness to 'the other' in 'the other's' own terms, whereas in School B the same imperative towards 'the other' is framed within the auto -referential framework of being and doing Jewish.